Des illusions sensorielles qui disent le futur ? Les clés des songes au XVIIe siècle - Juliette Lancel (Etudes Epistémè)
The purpose of treatises on dream interpretation is to offer seventeenth-century readers the means of interpreting their dreams to predict the future. In these treatises, the five senses help to clarify and to describe an element of the dream that may have a decisive importance in the upcoming interpretation. But by encouraging the readers to wonder about their sensory memories of the dream experience, these treatises on dreams also inform us about how to consider the different senses and the hierarchy that is attached to them. The books of dreams thus account for an ordering of the world.